Historicizing 1971 genocide : state versus person - Ahmed, Imtiaz, 1958- (Dhaka : University Press, 2009)
On indiscriminate killing of the faculty, students, and staff of Dhaka University in 1971 as part of suppressing the democratic movement; includes personal narratives.
Includes bibliographical references.
Keywords: University of Dhaka -- Anecdotes; Bangladesh -- History -- Revolution, 1971 -- Atrocities; Bangladesh -- History -- Revolution, 1971 -- Personal narratives